THE INFLUENCE OF MOTIVATION, TRAINING AND ORGANIZATIONAL CULTURE ON THE PERFORMANCE OF KTM RESORT BATAM EMPLOYESS - Jhovie Pratama Putra; Asron Saputra (SEAN Institute, 2023)
This study aims to determine whether motivation, training and organizational culture affect employee performance. The number of respondents was 105 consisting of all KTM resort Batam employees using SPSS version 25 as a statistical tool. The method by analyzing the influence of independent variables with the condition that the variables are not symmetrical is called associative. Associative can also be said to be a method that tests the relationship of more than one variable. The results show that the independent variables simultaneously affect employee performance with a calculated f value of 86.416 > 2.69 f table and sig <0.05 followed by a large number of influences of 71.1% and the remaining 28.9% outside of this study.